SaaS ERP Adoption Intent: Explaining the South African SME Perspective - (:unkn) unknown (My University, 2012)
This interpretive research study explores intention to adopt SaaS ERP software within South African SMEs. Semi-structured interviews with participants from different industry sectors were performed and seven multidimensional factors emerged explaining the current reluctance to adoption. While, improved IT reliability and perceived cost reduction were seem as benefits they were dominated by other reasons. Reluctance to adopt was attributed to systems performance and availability risk; sunk cost and satisfaction with existing systems; data security risk; loss of control and lack of vendor trust; and finally functionality fit and customization limitations. The findings provide new insights into the slow SaaS ERP adoption in South Africa and provide empirically supported data to guide future research efforts. Findings can be used by SaaS vendors to address perceived shortcomings of SaaS ERP software.
Keywords: African Research